Maternal exposure to chronic, low-dose nonylphenol in zebrafish: Disruption of ovarian health, reproductive function, and embryogenesis - Samanta, Anwesha; Biswas, Subhasri; Ghosh, Sandip; Banerjee, Sambuddha; Dam, Bomba; Maitra, Sudipta (Journal of environmental management, 2025)
Nonylphenol (NP), a non-ionic surfactant and potent endocrine disruptor, is known for its environmental persistence, biotic accumulation potential and toxicity. Nonetheless, mechanisms underlying NP modulation of female fertility with potential impact on embryogenesis in the unexposed offspring remain elusive. This study investigates the effects and toxic mechanisms of maternal exposure to NP at varying concentrations (50 and 100 μg/L) on zebrafish (Danio rerio), specifically focusing on ovarian health, reproductive parameters, and early developmental potential in the F1 generation. Our findings indicate a higher accumulation of NP in the ovaries compared to muscle tissue. Further, chronic (28 days) NP exposure promotes ovarian reactive oxygen species (ROS) accumulation, activates the MAPK (JNK, p38 MAPK, ERK1/2) pathways, AP-1 induction, and elevated expression of pro-inflammatory cytokines (Tnf-α, Il-1β, Il-6) triggering inflammation. Besides, heightened follicular atresia in NP-treated ovaries relates to increased Bax/Bcl2 ratio, cleaved caspase 3 and Parp1 activation prompting apoptosis. While it showed higher affinity to zebrafish ERα (in silico analysis), NP exposure in vivo promotes a robust increase in ovarian ERα but abrogated ERβ expression and a significant alteration in fshr and lhcgr transcripts. While attenuated StAR and P450 aromatase expression at both mRNA and protein levels and reduced igf3 expression reveal impaired ovarian microenvironment, NP-induced dysregulated NO/NOS/cyclooxygenase signaling and attenuation of hCG-induced p34cdc2 activation and oocyte maturation correspond well with decreased fecundity and fertilization efficiency. Intriguingly, maternal exposure to NP resulted in delayed embryogenesis, developmental aberrations, and reduced hatching rates in the unexposed offspring, risking F1 generation. Collectively, this study provides mechanistic insights into the detrimental influence of maternal exposure to NP on ovarian dysfunction, reproductive insufficiency and embryotoxicity. [Display omitted] •NP accumulation is higher in zebrafish ovaries than in muscle.•NP induces ovarian ROS, MAPK activation, inflammation, and follicular atresia.•NP shows the highest binding affinity to zebrafish ERα in silico.•NP disrupts ovarian ER homeostasis, endocrine factors, IGF axis, and oocyte maturation.•NP attenuates ovarian NO/Cox-2 axis, fertility, and embryonic development in offspring.